2018
DOI: 10.1007/s00277-018-3383-9
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes of total body irradiation plus cyclophosphamide versus busulfan plus cyclophosphamide as conditioning regimen for acute lymphoblastic leukemia: a comparative study

Abstract: The role of total body irradiation (TBI) in allogeneic hematopoietic stem cell transplantation (HCT) for adult acute lymphoblastic leukemia (ALL) remains controversial. Therefore, we investigated long-term treatment outcomes of transplanted ALL patients aiming to identify prognostic factors and the impact of conditioning. We enrolled consecutive ALL patients transplanted from 1990 to 2016, following TBI- or busulfan (Bu)-based conditioning regimen. We studied 151 ALL patients transplanted in first complete rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 29 publications
3
16
0
Order By: Relevance
“…In addition to the present larger study, we had also found a univariate association between TA‐TMA and TBI‐based conditioning in a smaller study of TA‐TMA in our population . It should be noted that TBI‐based conditioning has shown excellent results of survival and safety in our center, especially in patients younger than 40 years of age, as previously described . Other clinical predictors under consideration are infections.…”
Section: Discussionsupporting
confidence: 86%
“…In addition to the present larger study, we had also found a univariate association between TA‐TMA and TBI‐based conditioning in a smaller study of TA‐TMA in our population . It should be noted that TBI‐based conditioning has shown excellent results of survival and safety in our center, especially in patients younger than 40 years of age, as previously described . Other clinical predictors under consideration are infections.…”
Section: Discussionsupporting
confidence: 86%
“…SOS/VOD disease of the liver has been traditionally considered a severe complication of allogeneic HCT, particularly in patients with known risk factors [42]. Although it manifests as a rare HCT complication thanks to advances in transplant modalities [43,44], calicheamicin-conjugated antibodies, gemtuzumab and inotuzumab ozogamicin, have led to renewed interest in this syndrome [45,46]. Our group along with others has shown that changes in coagulation and fibrinolysis are predictive of SOS/VOD [47].…”
Section: Endothelial Injury Syndromesmentioning
confidence: 95%
“…100 In patients younger than 40 years, TBI provides better 5-year OS (55.1%, p=0.023) and disease-free survival (DFS) (48.6%, p=0.020) outcomes than busulfan-based conditioning regimens. 101 The EBMT Acute Leukaemia Working Party showed that the combination of TBI with etoposide is as effective as combination with cyclophosphamide (HR 0.62, p=0.04). 102 In a retrospective analysis from Japan, intravenous busulfan + cyclophosphamide had comparable outcomes with TBI-based regimens in ALL.…”
Section: Conditioning Regimens For Allogeneic Haematopoietic Stem Cell Transplantationmentioning
confidence: 99%